Perfiles de la sexualidad : a propósito de las diferencias entre hombres y mujeres en Colombia - Sevilla Casas, Elías (El Colegio de México A.C., 1997)
This article is a descriptive exercise as well as a substantive and methodological critique of the sexual behavior profile of Colombians in general as it is represented by two survey variables considered by specialits to be of great importance: age at firts intercourse (adulthood), and number of sexual partners during the year prior to the survey. A systematic comparison between Colombian behavior and behaviors in two contemporary surveys conducted in France and the United States reveals for the Colombian case a strong contrast between men and women (dimorphism) where men are more precocious and prefer multiple sexual partners, and women are less so. This finding is used as an excuse to put forward a series of considerations about the past reticence, and the current interest of sociology in the topics of sexuality, eroticism and love; the methodological difficulties of survey-based studies, and possible alternatives for clarifying questions posed by such dimorphism in Colombia. It is conclude that the survey-based studies need to be enriched with other ethnographic strategies (some of them indirect), in order to refine common hypothesis such as patriarchal domination. Mention is made of the necessary complicity by women for male domination to exist; the potential of subcultural and subregional studies within the historical structure of socioracial inequality is reviewed, and the apparently close relation between sexuality and violence is discussed. In the last part of the article, it is suggested that irl the case of Colombia, known throughout the world as a violent country, we could resort to the alternative of delving more deeply into "how men and women love one another", along the lines of the saying "tell me how you love and I'll tell you who you are", for the purpose of taking a rest from the scores of articles that ask "how do they kill one another?”